Relationship Between Simple Carbohydrate Intake and Increased Risk Of Comorbidity in Urban Adults - Rizky Mawaddah Hasibuan; Eka Febriyanti (UMSU, 2026)
Introduction: Obesity is an increasingly pressing health problem in various parts of the world, with a sharp increase in prevalence in both developed and developing countries. The risk of comorbidity is mainly associated with central obesity, which can be measured by Body Mass Index (BMI) and waist circumference. Simple carbohydrates, with a high glycemic index, are one of the factors that contribute to the accumulation of visceral fat, which can increase the risk of comorbidity. This study aims to explore the relationship between simple carbohydrate intake and increased risk of comorbidity in urban adults. Method: The research method used is descriptive analytical with a cross- sectional study design. Results: Based on the chi square statistical test results table, it was found that the higher the frequency of simple carbohydrate consumption, the higher the risk of comorbidity. So, the value with p = 0.01 (p0.05). Discussion: There is a relationship between simple carbohydrate intake and an increased risk of comorbidities in urban adults. Further research is needed to balance the respondents and is expected to provide sufficient information as well as identifying the types of simple carbohydrates studied regarding the nutritional adequacy rate of simple carbohydrates.